DEGENERATIVE SPINE INJURY ASSOCIATED WITH BACK PAIN: MORPHOGENETIC ASPECTS - N. G. Pravdyuk; N. A. Shostak (Klinicist)
Degeneration of the intervertebral disk (IVD) is a pathological process resulting from an interplay between genetic and environmental factors causing structural and functional damage of the IVD and neighboring structures. It is the first stage of degenerative cascade in the vertebral motion segment. Initiation and progression of IVD degenerative processes traditionally involves several factors: inadequate mechanical load, decreased diffusion of nutrients through the arch laminae, and genetic factors playing a significant role in the development  of degenerative changes. Three categories of candidate genes whose coding variants are associated with different forms of degenerative changes in the IVD are identified, a conceptual model of genetic interactions in degenerative disease of the disk is developed. The study  of the role of structural changes in back pain genesis, evaluation of risk factors allow to optimize the tactics of patient care and find new therapeutic solutions preventing disease progression.